Hubungan Pengetahuan Tentang Kanker Payudara dengan Perilaku Pemerikasaan Payudara Sendiri (SADARI) pada Siswi di SMA Muhammadiyan 1 Masaran - Desti Pramudika Romadhoni; Titik Haryanti; Dewi Puspito Sari (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2023)
In Central Java in 2019 there were 702 cases of breast cancer, while in 2019 there were 42 cases of breast cancer in Sragen Regency. One of the factors causing the still high number of cancer cases is the low level of behavior in carrying out BSE. The results of a preliminary study conducted at SMA Muhammadiyah 3 Masaran, of the 10 female students (100%) none knew about the importance of BSE and none had ever done BSE once a month. The aim of this research was to determine the relationship between knowledge about breast cancer and breast self-examination behavior (BSE) among female students at SMA Muhammadiyah 3 Masaran. This research is quantitative with a cross sectional approach.